OPTIMALISASI HEALTH LITERACY MELALUI BERMAIN PADA PERILAKU HIDUP BERSIH DAN SEHAT ANAK PRA SEKOLAH - Rukmini, Rukmini; Ramadhani, Dwi Yuniar; Mamesah, Marline Merke; Syaiful, Yuanita (Community Development in Health Journal, 2024)
Introduction & Aim: The level of children's health is related to health problems about infection factors. Health efforts are carried out in the form of promotive, preventive, curative, and rehabilitative, in the form of Clean and Healthy Behavior (Perilaku Hidup Bersih dan Sehat, PHBS). The aim was to improve PHBS skills in children: Washing hands in 6 steps and sorting and disposing of waste properly. Implementation Method: The activity was held in January - February 2024 at PAUD Kuncup Melati RW 07, Kapasan, Simokerto, Surabaya for 33 pre-school age students. The initial survey has formulated problems and solutions in the form of efforts to prevent disease in early childhood with PHBS through health literacy using the train-playing method. Arranging permits, determining the location and target participants, socializing the original activities, and preparing the media. Method of Activity: There was a Health station which consisted of station 1: Hand Washing Movement and Song and the next station was to dispose of rubbish properly in the Hygiene Box. Evaluation has been done at the 4th meeting and at the same time rewards in the form of healthy, nutritious snacks. Results: Participation through play-based health literacy has been shown to increase young children's ability to participate in PHBS activities. namely washing their hands in 6 steps correctly, which initially 100% of students were not able to do correctly to 84.8% of students who were able to do it correctly. Discussion: Health Literacy using the play method can increase PAUD students' understanding and ability to carry out Clean and Healthy Living Behaviors, namely washing their hands in 6 steps correctly and being able to sort and dispose of waste in the correct place. PHBS that can be done early and continuously will become a good habit for children.